A two-layer data envelopment analysis model for sustainable performance evaluation - Zalatar, Willy F. (Animo Repository, 2019)
Data envelopment analysis is a popular method of evaluating the performance of almost all types of organizations. The aim of this paper is to construct a twolayer DEA model which can be utilized to evaluate the sustainable performance of a manufacturing company based on its degree of leanness. The lean indices are treated as virtual inputs while the sustainability indices are considered as virtual outputs. Empirical results indicated that efficient companies scored high in Human Resources and Supplier and Customer Relationships as well as in Economic and Social Performance. This paper highlights the positive effects of adopting lean manufacturing practices on a company's sustainable performance. © 2018 IEEE.